Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak UMKM - Mulyani, Arik Tri; Marsuking, Marsuking; Suryono, Abi; Hidayah, Nila (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2022)
Micro, Small and Medium Enterprises (MSMEs) are one of the state revenues from the tax sector, which has potential for Indonesia's economic growth. The current development of MSMEs can also be a potential and opportunity for tax revenue. However, it also has challenges if it is not balanced with taxpayer compliance in fulfilling tax obligations. This study aims to determine the factors that affect taxpayer compliance in paying MSME taxes in Bantul City. Taxpayer compliance factors include knowledge and understanding of taxation, taxpayer awareness, modernization of the tax administration system, and tax sank . This research uses quantitative research methods. The sample selection method, Purposive Sampling using the solving formula, obtained 95 samples of MSME actors per the established criteria. The data analysis technique used is Multiple regression linear analysis using Version 28 software. The results showed that knowledge and understanding of taxation, taxpayer awareness, modernization of the tax administration system and tax sank si had a positive and significant effect on taxpayer compliance in paying MSME taxes. Meanwhile, partial knowledge and understanding of taxation, taxpayer awareness, and modernization of the tax administration system positively affect taxpayer compliance. Still, tax sanctions hurt taxpayer compliance in paying MSME taxes in Bantul Regency.